2012
DOI: 10.29252/jnkums.4.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Depression in male patients with systolic heart failure and related factors

Abstract: Background & objective: Depression associate with increase severity of illness, length of hospitalization and mortality in heart failure patient's .The aim of this study was to investigate the frequency and related factors of depression in male systolic heart failure patients. Materials & Methods: This is a cross sectional study that was conducted on 100 male patients with systolic heart failure in Alborz of Karaj and Shahriar Social Security Hospitals in 2010. Sampling method in this study was Convenience sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For example, drugs that significantly contributed to ED in HF patients were from the classes of cardiac glycosides, ACEI, beta blockers, and diuretics (Zeighami Mohammadi, Shahparian, Fahidy, & Fallah, 2012). As this brief overview of cardiac medications illustrates, some classes of drugs may cause sexual side effects more than others.…”
Section: Medications and Sexual Functionmentioning
confidence: 98%
“…For example, drugs that significantly contributed to ED in HF patients were from the classes of cardiac glycosides, ACEI, beta blockers, and diuretics (Zeighami Mohammadi, Shahparian, Fahidy, & Fallah, 2012). As this brief overview of cardiac medications illustrates, some classes of drugs may cause sexual side effects more than others.…”
Section: Medications and Sexual Functionmentioning
confidence: 98%
“…Similarly, CCBs and cardiac glycosides overall do not seem to adversely affect sexual function (Nicolai et al, 2014), although digoxin use was significantly associated with erectile dysfunction in patients with heart failure in one report (Zeighami Mohammadi et al, 2012). Choosing a diuretic becomes a more difficult clinical issue, because as mentioned earlier, thiazides and aldosterone antagonists are long known to contribute to sexual dysfunction, and the present results illustrate that loop diuretics may cause adverse effects as well.…”
Section: Implications For Practicementioning
confidence: 80%
“…Further understanding of the role of multiple medications, as well as other contributing factors such as the particular cardiac diagnosis and comorbidities merits further study. There is some indication that patients with heart failure or stroke may have greater sexual side effects and in multiple drug classifications (Bugnicourt et al, 2014;Zeighami Mohammadi, Shahparian, Fahidy, & Fallah, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that obesity increases the risk of chronic diseases such as diabetes, cardiovascular disease, stroke, musculoskeletal disorders such as arthritis, and some cancers (Dixon, One of the complications faced by obese individuals is sleep problems, which has received limited attention. Sleep is a basic human needs and is necessary to maintain the energy of appearance, coordination of body rhythm, and physical health (Akbari, Mirzaei, & Azizi, 2016;Zeighami Mohammadi & Shahparian, 2012). Studies have shown that sleep deprivation leads to a decrease in daily performance, impairment of metabolic function, disruption of the immune system and cortisol and insulin levels, and increased mortality (Mai & Buysse, 2008).…”
Section: Introductionmentioning
confidence: 99%